2011
DOI: 10.1890/es10-00199.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of acute and long-term vehicle exposure on physiology and reproductive success of the northern spotted owl

Abstract: Abstract. Stress physiologists posit that multiple simultaneous demands faced by an organism may have non-additive effects on the magnitude of their response to disturbance. The environmental assessment literature emphasizes a similar phenomenon at the population level, arguing that populations can compensate for perturbations up to a threshold, beyond which disturbance impacts may be greatly magnified-and even cause system collapse. We integrated these two approaches to examine the roles of environment, life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 44 publications
2
49
1
Order By: Relevance
“…Species that do not show avoidance may still be negatively impacted from chronic noise, for example impacts on passerines include reduced pairing success (Habib et al 2007) and reduced fitness (Halfwerk et al 2011, Schroeder et al 2012. Spotted Owls nesting near noisy roads have been found to fledge fewer young than owls nesting near quiet roads (Hayward et al 2011). Future research should assess the reproductive success of owls living in noisy areas to determine if chronic industrial noise has other negative impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species that do not show avoidance may still be negatively impacted from chronic noise, for example impacts on passerines include reduced pairing success (Habib et al 2007) and reduced fitness (Halfwerk et al 2011, Schroeder et al 2012. Spotted Owls nesting near noisy roads have been found to fledge fewer young than owls nesting near quiet roads (Hayward et al 2011). Future research should assess the reproductive success of owls living in noisy areas to determine if chronic industrial noise has other negative impacts.…”
Section: Discussionmentioning
confidence: 99%
“…A study on Spotted Owls (Strix occidentalis) found they will flush from nests more frequently with increased proximity to a noise source (Delaney et al 1999). Two other studies on physiological responses of Spotted Owls to anthropogenic noise found elevated fecal glucocorticoids (Hayward et al 2011), but no detectable increase in fecal corticosterone (Tempel et al 2003). These studies on Spotted Owls applied temporary noise stimuli, e.g., helicopters, chainsaws, or motorcycles, so it is not known how owls respond to a permanent noise source on the landscape.…”
Section: Introductionmentioning
confidence: 94%
“…We assessed several non-invasive indicators of representative physiological functions related to condition (Hayward et al, 2011;Mormede et al, 2007). One of them was fecal cortisol metabolites (CORT) which were used to index stress levels.…”
Section: Acth Challengementioning
confidence: 99%
“…Thus, the interpretation of GC levels might require complementary information on the state of reproduction and other relevant physiological functions such as immunity and nutritional conditions (Romero, 2004). In this sense, some authors have highlighted the importance of considering the trade-offs between stress response and fitness correlates of condition to accurately interpret GC or GCm results for conservation issues (Busch and Hayward, 2009;Hayward et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring these impacts in nature can be difficult, however, because warmer ambient temperatures and environmental exposure may also hasten fGC degradation, and both temperature and exposure effects are likely to vary with time of year [15]. Nutritional status, which is likely to vary with time of year, can also be detected through fGC levels [2], [5], [10], [16], [17]. Yet, diet composition itself can impact steroid excretion rates [18]–[21].…”
Section: Introductionmentioning
confidence: 99%